Effect of iron on growth and lipid accumulation in Chlorella vulgaris - Liu, Zhi-Yuan; Wang, Guang-Ce; Zhou, Bai-Cheng (Bioresource technology, 2008)
The economic feasibility of algal mass culture for biodiesel production is enhanced by the increase in biomass productivity and storage lipids. Effect of iron on growth and lipid accumulation in marine microalgae Chlorella vulgaris were investigated. In experiment I, supplementing the growth media with chelated FeCl 3 in the late growth phase increased the final cell density but did not induce lipid accumulation in cells. In experiment II, cells in the late-exponential growth phase were collected by centrifugation and re-inoculated into new media supplemented with five levels of Fe 3+ concentration. Total lipid content in cultures supplemented with 1.2 × 10 −5 mol L −1 FeCl 3 was up to 56.6% biomass by dry weight and was 3–7-fold that in other media supplemented with lower iron concentration. Moreover, a simple and rapid method determining the lipid accumulation in C. vulgaris with spectrofluorimetry was developed.